Examining the contribution of logistics and supply chain in boosting oman's trade network - Ashraf Mishrif; Alessandro Antimiani; Asharul Islam Khan (Economies, 2023)
Economic integration, which in today's global trade is the fundamental component of linking economic ties between countries, is another important factor in the acceleration of economic growth. The provision of trade logistics services is essential to a nation's economic success in international trade activities. It is essential for enterprises engaged in active international trade to achieve competitive advantages. The international trade and localised commercial activity, to a large extent, is dependent on the logistics and supply chain infrastructure and operational capacity. However, the area received little attention from the perspective of applied economics. The in-depth empirical studies on the impacts of logistics on trade efficiency are few and limited. The study aims to investigate the role of logistics and supply chains in international and national trade in a developing country. It uses secondary data for the analysis. The model and software used in the study are the gravity model and GTAP10a. The time horizon used spans 2014-2030. The results show that in order to enhance trading and commercial activities, a developing country should develop logistics and supply chain infrastructure, train people, and design a flexible logistics policy.
Keywords: 330; free trade agreement; trade network; trade infrastructure; logistics; supply chain